The Distribution of Cytotoxic Necrotizing Factors (CNF-1, CNF-2, CNF-3) and Cytolethal Distending Toxins (CDT-1, CDT-2, CDT-3, CDT-4) in Escherichia coli Isolates Isolated from Extraintestinal Infections and the Determination of their Phylogenetic Relationship by PFGE - Cansu Onlen Guneri; Fatih Koksal; Suna Kizilyildirim; Basak Bedir; Togrul Nagiyev (International Journal of Clinical Practice)
Backgrounds. Diagnostic markers of extraintestinal infection in Escherichia coli (E. coli) remain unclear in the literature. Extraintestinal pathogenic E. coli (ExPEC) is differentiated from other E. coli isolates in terms of virulence factors, such as host cell adhesion, invasion, cytotoxic necrotizing factor (CNF (cnf1-cnf3)) and cytolethal distending toxin (CDT (cdt1-cdt4) that are responsible for cell death. We aimed to investigate the frequency of CNF-CDT and the relationship between the clinical diagnosis and genotypes in E. coli isolates with different clinical origins. Methods. A total of 646 E. coli isolates (obtained from 645 patients) isolated from different infection sites other than the intestine were evaluated in aspects of the CNF, CDT virulence genes, phylogenetic grouping, and phylogenetic relationship by using PCR and PFGE. Results. At least one virulence gene was present in 156 (24%) of the 646 ExPEC isolates. We detected cnf1, cnf2, and cnf3, in 78, 12, and 20 ExPEC isolates, respectively. Also, cdt1, cdt2, cdt3, and cdt4 genes were present in 20, 4, 4, and 4 isolates, respectively. Some isolates harbored more than one gene, being cnf1-cnf3 (n = 6), cnf1-cdt1 (n = 4), and cdt1-cdt4 (n = 4). These 156 isolates were distributed into 106 large clusters by PFGE. Virulent ExPEC is primarily related to groups B2 (60%) and D (32%). Conclusion. To our knowledge, this study demonstrated the presence of cnf2, cnf3, cdt1, cdt2, cdt3, and cdt4 genes for the first time in the literature for Turkey. The widespread presence of the CNF gene in E. coli helps distinguish ExPEC from commensal isolates.